(untitled) (Iranian Journal of Kidney Diseases, 2022)
Introduction. Association of constipation with incomplete bladder emptying, functional bladder outlet un-coordination, urinary tract infection (UTI), and upper urinary tract dilatation has been reported. We designed a study to determine the impact of chronic functional constipation on kidney and bladder ultrasound parameters, the results of the uroflowmetry test, and its association with UTI. Methods. The study group consisted of 24 cases and 48 controls, who were children between 5 to 18 years-old, from June 2017 to June 2018. The case group included children with chronic functional constipation. The healthy children with urinary continence and regular bowel habits without any history of UTI were considered as the control group. The variables were bladder volume, postvoiding urinary residual volume, full and empty bladder wall thicknesses, uroflowmetry parameters and, UTI prevalence. Results. There were no significant differences in the prevalence of UTI, upper urinary tract dilatation on kidney ultrasound, uroflowmetry and, bladder ultrasound parameters between the case and control groups (P > .05 for all). We found abnormal uroflowmetry curves in 58.3% and 35.4% of the case and control groups, respectively (P > .05) and a higher rate of staccato curves in constipated compared to healthy children. Conclusion. the prevalence of UTI and upper urinary tract dilatation on kidney ultrasonography are not significantly different between constipated and healthy children. Moreover, it seems that chronic constipation has no significant impact on the storage and emptying functions of the bladder. The higher frequency of staccato curves in constipated compared to healthy children can indicate that fecal mass causes detrusor sphincter dyssynergia. DOI: 10.52547/ijkd.6568